A Study on the Price Spatial Differentiation and Influencing Factors of Rural Homestay in Suzhou Based on the Hedonic Price Model - Sheng Yang; Lei Wang; Yu Bi (Buildings)
Using ArcGIS software to conduct spatial autocorrelation analysis, it was found that the price distribution of rural homestays in Suzhou is not random but shows apparent spatial clustering. Among the 81 rural homestays were 9 high-high clusters, 25 low-low clusters, 1 high-low outlier, and 5 low-high outliers. The hedonic price model is an economic model that breaks down goods or services into multiple attributes to estimate their prices. Based on this model, this paper further investigates the differentiated impacts and interactions between internal accommodation characteristics and external environmental attributes in the pricing mechanism of rural homestays in Suzhou. The results show that (1) the high-priced rural homestays in Suzhou are concentrated in the lake island resort with good natural environment and perfect infrastructure; (2) the location, facility quality, and network score of rural homestays have a positive impact on housing prices; (3) the parking lot of rural homestays hurts housing prices; (4) the quality of rural residential buildings and facilities has the most significant positive impact on housing prices. By comparing the hedonic price model of rural homestay and the heterogeneous preferences of consumers, this study provides rural homestay operators with effective room pricing strategies and marketing implications, provides policymakers with reference factors to promote the development of rural homestay industry, and has specific guiding significance for the sustainable development of the homestay industry.